(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
This research was driven by the low score of mathematics in fractions and decimals at MI Negeri 1 Banyumas. The ability of students during the pandemic transition is different from students who attended school before the pandemic. This is known from the average daily test scores on fractions and decimals problems. Therefore, this study aims to analyze: (1) the types of errors and (2) the proportion of errors made by students in solving fractions and decimals problems in terms of the Nolting Theory. This research is a field research involving 28 grade IV students at MI Negeri 1 Banyumas as a subject. The data obtained from the results of tests and interviews with students. Data analysis was carried out using a quantitative descriptive approach to describe the types of errors and the proportion of each error. The results showed that of the 28 grade IV MI Negeri 1 Banyumas students, several types of errors were found, namely misdirection errors, careless errors, conceptual errors, application errors, test taking errors, and study errors. Quantitatively the largest proportion of errors in each number are careless errors.